Ukrainian agriculture at risk as the European Union's liberalized trade measures expire - Glauber, Joseph W.; Welsh, Caitlin; Dodd, Emma (Center for Strategic and International Studies, 2025)
The expiration of wartime trade exemptions by the European Commission on Ukrainian food imports could compound challenges for Ukrainian producers, who are now facing their fourth-straight growing season in wartime conditions.